Implementing a flipped model of instruction in the EFL listening classroom: Impact on comprehension - Ehsan Namaziandost; Zohreh Rezaei; Parisa Etemadfar; Samir Alekasir (Institut Agama Islam Negeri (IAIN) Palangka Raya, Indonesia, 2020)
Inventive technologies have provided students greater ways to invest more productive time within the classrooms, such as listening class. However, the flipped model of instruction should be practiced as a way to engage students in the process of listening comprehension. This experimental study aimed to investigate the effects of the flipped classroom (FC) on advanced EFL learners’ listening comprehension. Sixty Iranian advanced EFL learners (19 to 23 years old) participated in 14 sessions. Half of the students taught through the flipped model of instruction (experimental group) and the others through traditional instruction (control group). Using a before and after design, students were retested after seven weeks. Results showed that the means average resulted from the L2 listening comprehension test revealed those both groups showing increases in listening scores, but the experimental group’s mean score was higher than in the control group. Therefore, the FC model's implementation in the context of teaching and learning L2 listening comprehension can lead to positive outcomes since they could engage students in the process of learning English. The implication of this study calls for the FC model implementation to engage students in listening comprehension in the chance to learn better and expand their educational knowledge.